Non-Invasive Approach to Harmonic Responsibility Assignment Based on Conservative Power Theory - Arcadepani, Matheus B. [UNESP]; Moreira, Alexandre C.; Morales-Paredes, Helmo K. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This letter introduces a novel approach to responsibility assignment in harmonic generation, grounded in Conservative Power Theory (CPT). The methodology is derived through an analysis of the CPT’s residual current component. To demonstrate the effectiveness of the approach, a comparison is carried out with the methodologies presented in (Gianesini et al., 2023), revealing that, although the interpretations are analogous, the proposed approach stands out for its remarkable simplicity and ease of implementation, providing significant advantages in terms of practical application. In contrast to methods documented in the literature, the method proposed in this letter exclusively utilizes voltage and current measurements obtained at a single point, thus characterizing it as a non-invasive method. This characteristic eliminates the need to determine the harmonic impedances of the system or install passive or active elements.
Keywords: Conservative power theory; harmonic generation; non-invasive method; responsibility assignment